Arabidopsis lipid droplet‐associated protein (LDAP) – interacting protein (LDIP) influences lipid droplet size and neutral lipid homeostasis in both leaves and seeds. (27th November 2017) - Pyc, Michal; Cai, Yingqi; Gidda, Satinder K.; Yurchenko, Olga; Park, Sunjung; Kretzschmar, Franziska K.; Ischebeck, Till; Valerius, Oliver; Braus, Gerhard H.; Chapman, Kent D.; Dyer, John M.; Mullen, Robert T.
Summary: Cytoplasmic lipid droplets (LDs) are found in all types of plant cells; they are derived from the endoplasmic reticulum and function as a repository for neutral lipids, as well as serving in lipid remodelling and signalling. However, the mechanisms underlying the formation, steady‐state maintenance and turnover of plant LDs, particularly in non‐seed tissues, are relatively unknown. Previously, we showed that the LD‐associated proteins (LDAPs) are a family of plant‐specific, LD surface‐associated coat proteins that are required for proper biogenesis of LDs and neutral lipid homeostasis in vegetative tissues. Here, we screened a yeast two‐hybrid library using the Arabidopsis LDAP3 isoform as 'bait' in an effort to identify other novel LD protein constituents. One of the candidate LDAP3‐interacting proteins was Arabidopsis At5g16550, which is a plant‐specific protein of unknown function that we termed LDIP (LDAP‐interacting protein). Using a combination of biochemical and cellular approaches, we show that LDIP targets specifically to the LD surface, contains a discrete amphipathic α‐helical targeting sequence, and participates in both homotypic and heterotypic associations with itself and LDAP3, respectively. Analysis of LDIP T‐DNA knockdown and knockout mutants showed a decrease in LD abundance and an increase in variability of LD size in leaves, with concomitant increases in total neutral lipid content. Similar phenotypes were observed in plant seeds, which showed enlarged LDs and increases in total amounts of seed oil. Collectively, these data identify LDIP as a new player in LD biology that modulates both LD size and cellular neutral lipid homeostasis in both leaves and seeds. Significance Statement: While recent studies have highlighted cytoplasmic lipid droplets (LDs) as being more than simply inert lipid storage depots in oilseeds, the cellular machinery involved in LD formation and function in plants, particularly in non‐seed cell types, is relatively unknown. Here we report the identification and characterization of a protein, LDIP, which interacts with the LD surface and is involved in regulating LD size and neutral lipid homeostasis in both leaves and seeds in Arabidopsis.